The Effect of Bottom Ash on the Compressive Strength and Tensile Strength of HVFA Concrete - Januarti Jaya Ekaputri; Yusak Nurrizki (Universitas Islam Sultan Agung, 2023)
This paper focuses on the effects of High Volume Fly Ash (HVFA) concrete with high content Bottom Ash (BA) as a fine aggregate. A strength target of 45 MPa with 12 ± 2 cm slump concrete was determined as a control. The tests that carried out were compressive strength at the age of 3 to 90 days ages and splitting strength at the age of 28 to 90 days ages, slump test, measurement of heat of hydration, and concrete autogeneous shrinkage. Variations in the concrete mix tested were HVFA without BA with FA content of 50% - 80%, and HVFA with 50% BA as a sand replacement. The In general, the use of high volume BA in the HVFA mixture provided an increase in strength both at the initial age and final in all variations. The internal curing effect provided by BA accelerated the hydration and solidification process at the early age, thus giving the effect of increasing the mechanical properties of concrete. However, the acceleration of solidification was accompanied by the increase in the shrinkage. BA properties which have greater absorption compared to sand also caused the workability decreased.